The effects of basil (Ocimum basilicum) leaf extract on Ca9-22 oral cancer cells - Li, Min; Wang, Yueyan; Bao, Yan (Archives of Biological Sciences, 2024)
Paper description: Studies have described basil extract's antioxidant, anti-inflammatory, and cytotoxic effects against various cancers. Limited research has explored it in oral cancer. This study assessed the effects of ethanolic basil leaf extract on Ca9-22 oral cancer cell viability, cell cycle progression, and inflammation using the MTT assay, real-time-polymerase chain reaction (RT-PCR), and the enzyme-linked immunosorbent assay (ELISA). Basil (Ocimum basilicum) extract inhibited cell viability by arresting the cell cycle and suppressing inflammatory genes. This research provides novel insights into basil extract’s anti-proliferative and anti-inflammatory mechanisms in oral cancer. Abstract: Basil (Ocimum basilicum), as a prominent member of the Lamiaceae family, is known to possess anti-inflammatory, anti-oxidant, and anti-cancer properties. This study investigated the inhibitory effect of basil extract on oral cancer cells. Basil leaves were dried and extracted with ethanol. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay was used to assess the cytotoxic effect of basil extract (12.5, 25, 50, 100, 200, 500, and 1000 μg/mL) on Ca9-22, a human gingival squamous carcinoma cell line, after 24, 48, and 72 h. Gene expression of cell cycle regulators (cyclin D1, cyclin-dependent kinase 4 (CDK4), p21, p53) and inflammatory markers (cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), tumor necrosis factor-alpha (TNF-α), interleukin (IL)-1β and IL-6) was analyzed using real-time polymerase chain reaction (RT-PCR). Additionally, these markers were measured in culture supernatants via enzyme-linked immunosorbent assay (ELISA). The MTT assay revealed a concentration-dependent reduction in cell viability, with IC50 values of 350 μg/mL for Ca9-22 cells. RT-PCR analysis revealed that treated cells exhibited downregulation of cyclin D1 and CDK4, along with upregulation of p21 and p53, compared to control Ca9-22 cells, which were only exposed to nutrient medium. These changes were observed at both mRNA and protein levels. Inflammatory genes (COX-2, iNOS, TNF-α, IL-1β, IL-6) were significantly decreased at both mRNA and protein levels. Basil extract exerts cytotoxic effects on oral cancer cells by inhibiting cell cycle progression and inflammatory mediators. These findings point to the potential use of O. basilicum extract as a therapeutic agent against oral cancer.